2003
DOI: 10.1093/bja/aeg237
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboendarterectomy in a case of hereditary stomatocytosis

Abstract: We present a case of pulmonary thromboendarterectomy performed successfully in a patient with stomatocytosis. Stomatocytosis is a rare condition of abnormal erythrocyte morphology in which haemolysis and hyperkalaemia occur at cooler temperatures. A 35-yr-old male with stomatocytosis was referred for pulmonary thromboendarterectomy in the context of chronic thromboembolic pulmonary hypertension. He had undergone splenectomy as a child, which rendered him hypercoagulable as the spleen normally removes the haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Indeed, intravascular hemolysis has been linked to pulmonary hypertension (19,24,26,45,59), systemic vasculopathies (27,28,50,52,53,60), and cardiovascular complications (11,25,30,39). Although such studies have suggested that CF-Hb likely plays important roles in vascular disease, the actual contribution of CF-Hb to disease pathology has drawn controversy, particularly in sickle cell disease (SCD) (9,18).…”
mentioning
confidence: 99%
“…Indeed, intravascular hemolysis has been linked to pulmonary hypertension (19,24,26,45,59), systemic vasculopathies (27,28,50,52,53,60), and cardiovascular complications (11,25,30,39). Although such studies have suggested that CF-Hb likely plays important roles in vascular disease, the actual contribution of CF-Hb to disease pathology has drawn controversy, particularly in sickle cell disease (SCD) (9,18).…”
mentioning
confidence: 99%
“…15,20 In addition, a similar prevalence of PH in patients with thalassemia who do not develop acute chest syndrome suggests that lung injury may worsen PH but certainly is not etiologic. Chronic thromboembolic PH has been reported in patients with hereditary spherocytosis and stomatocytosis 43,[47][48][49] and appears to occur in approximately 5% of patients with SCD and severe PH. 16 PH and two (2%) of 83 patients without PH died during a 2-year follow-up period.…”
Section: Smentioning
confidence: 99%
“…4 These mechanisms ultimately can produce a systemic proliferative vasculopathy, a hallmark of which is pulmonary hypertension that develops during adulthood. In support of the role of hemolysis as an important contributing mechanism in this disorder, PAH is an increasingly recognized complication of chronic hereditary and acquired hemolytic anemias including sickle cell disease, [5][6][7][8][9][10][11][12][13][14][15] thalassemia, [16][17][18][19][20][21][22][23][24][25] paroxysmal nocturnal haemoglobinuria, 26,27 hereditary spherocytosis and stomatocytosis, [28][29][30][31][32][33] microangiopathic hemolytic anemias, [34][35][36][37][38][39][40] pyruvate kinase deficiency, 41 and possibly malaria. 42,43 Additionally, certain other conditions are associated with both intravascular hemolysis and risk of pulmonary hypertension, such as schistosomiasis, 44,45 and iatrogenic hemolysis from mechanical heart valves, 46,47 left v...…”
Section: Hemolytic Anemia Associated Pulmonary Hypertensionmentioning
confidence: 99%
“…18,20,22 Although there are no formal epidemiologic data on the prevalence of PAH in other hemolytic disorders, several case series of PAH have been reported in patients with other inherited or acquired hemolytic disorders. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][44][45][46][47][48][49][50][51][52] Of note, a number of studies suggest that PAH may be more common in patients with thalassemia intermedia and E thalassemia than in patients with thalassemia major. This observation emphasizes the importance of chronic hemolysis in PAH pathogenesis, because patients with thalassemia major are transfused repeatedly and have minimal intravascular hemolysis 125 .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation